What Do Post-Pandemic Graduate Theses Reveal About Behavioral and Digital Addictions? A Bibliometric Analysis - Yılmaz, Tuğba; Koç, Yusuf Ziya; Kul, Melis (Addicta: The Turkish Journal on Addictions, 2025)
The aim of this study is to examine theses on addiction conducted in Türkiye. For this purpose, graduate theses related to addiction, covering the post-pandemic period from 2021 to 2024 and available in the National Thesis Center, were analyzed. Titles and contents containing the term “addiction” were identified using the keyword “bağımlı*.” A total of 1299 master’s theses, 178 medical specialization theses, and 126 doctoral theses were retrieved. After applying exclusion criteria to 195 theses with restricted access, 1604 studies were included in the evaluation. Using the document analysis method, data such as thesis numbers, authors, publication years, topics, sample age ranges, group sizes, types of addiction, and subcategories of addiction were entered into an Excel document and subsequently analyzed. Some key findings from the study are as follows: In 2018, there were 229 theses on addiction, which increased to 452 in 2019. During the pandemic year of 2020, the number dropped to 274 but rose again to 440 in 2021. In the following years, the number of theses on addiction was recorded as 398 in 2022, 463 in 2023, and 498 in 2024. The study examined substance-related, behavioral/digital, and other types of addictions, while non-psychological or non-psychiatric terms (e.g., addiction to educational materials) were excluded from the analysis. The findings indicate that the number of addiction-related theses increased after the pandemic, with a particularly notable rise in theses focusing on behavioral and digital addictions. This trend suggests that contemporary problem areas are reflected in academic research and investigated in theses required for specialization. The most common disciplines for addiction-related theses were identified as psychology, sports, education and instruction, family medicine, nursing, and psychiatry. Among addiction types, digital addictions were the most frequently studied, followed by substance-related addictions. Many addiction-related theses were at the master’s, doctoral, and medical specialization levels, whereas proficiency in arts theses paid significantly less attention to this topic.